Effect of liposome-treated red blood cells in an anemic rat model. (2nd January 2017) - da Silveira Cavalcante, Luciana; Feng, Qingping; Chin-Yee, Ian; Acker, Jason P.; Holovati, Jelena L.
Abstract: Context : Liposomes have been shown to improve human red blood cell (RBC) in vitro quality by minimizing membrane damage occurring during 42-d hypothermic storage. Small animal models are necessary to evaluate novel blood products and guide future clinical studies. Objectives : The aim of this study was to assess the effect of liposome treatments on rat RBC hypothermic storage lesion (HSL) and to examine in vivo outcomes of transfusing liposome treated RBCs in a rat model. Materials and methods : Unilamellar liposomes were synthesized which contained saturated (DPPC:CHOL, 7:3 mol%), unsaturated (DOPC:CHOL, 7:3 mol%), saturated charged (DPPC:CHOL:PS, 6:3:1 mol%), and unsaturated charged (DOPC:CHOL:PS, 6:3:1 mol%) phospholipids. After liposome treatment, rat RBC quality was assessed by percent hemolysis, deformability, aggregation, hematological indices, microvesiculation, and cholesterol/phospholipid concentrations. An anemic rat model of myocardial ischemia and reperfusion (I/R) was used to evaluate the outcomes of transfusing liposome-treated RBCs. Results: All four liposome treatments resulted in significant decreases in hemolysis, with the most prominent effect seen with DOPC-liposomes (DOPC: 1.6 ± 0.1% versus control: 3.1 ± 0.2%, p = 0.015). RBCs treated with uncharged liposomes had lower hemolysis compared with charged liposomes (3.4 ± 0.2% versus 3.9 ± 0.4%, p = 0.010). The in vivo study showed no significant difference in the hemoglobin levels and infarct size (53.3 ± 13.1% versus 45.3 ± 8.4%, p = 0.223) between liposome and control groups. Discussion and conclusion: Liposome treatment improved in vitro quality of stored rat RBCs. However, the changes observed in vitro were not sufficient to improve the in vivo outcomes of myocardial I/R in anemic rats transfused with liposome-treated RBCs.